Control over Self‐Doping in High Band Gap Perovskite Films. Issue 23 (7th June 2018) - Kulbak, Michael; Levine, Igal; Barak‐Kulbak, Einav; Gupta, Satyajit; Zohar, Arava; Balberg, Isaac; Hodes, Gary; Cahen, David
Abstract: It is reported how differences in the composition of high bandgap Pb bromide‐based perovskites affect their carrier diffusion length and junction type. Pb‐based, APbX3, halide perovskite (HaP) films and devices are studied, where A can be a mixture of formamidinium, methylammonium (MA), and Cs, and X a mixture of Br and Cl, using a combination of dark‐ and photoconductivity and steady‐state photocarrier grating. The results show the cation and anion compositions affect both majority and minority carrier diffusion lengths. In particular, using electron beam‐induced current measurements, FTO\dTiO2 mp‐TiO2 HaP\PTAA (poly‐triarylamine)\Au devices are studied. The results enable identifying junction and built‐in voltage formation and track position and size of the space charge region width with changes in the HaP composition. As far as it is known, it is found for the first time that a mixed‐cation HaP forms a junction that has characteristics of a p‐i‐n one, with relatively long and comparable carrier diffusion lengths, while the single cation‐based bromide HaPs form clear p‐n junctions at the interface with the TiO2 [pure CsPbBr3 and MAPbBr3 (Cl)] or a buried one (MAPbBr3 ) and shorter diffusion lengths. These differences are attributed to lower carrier density in MAPbBr3, and especially in the mixed cation HaP, which is comparable to iodide‐based HaP films. Abstract : Changing the cation composition in pure bromide halide perovskite films can cause variation of up to six orders of magnitude in the dark hole concentration in the layer. Furthermore, the space charge region and minority carrier diffusion length are affected by the number and type of cations in the material.